Conceptualizing, Measuring, and Mapping Contentiousness - Theresa Gessler; Swen Hutter (Contentious Episodes in the Age of Austerity: Studying the Dynamics of Government–Challenger Interactions, 2021)
Portugal and Spain were among the countries hardest hit by the global financial crisis that led to the eurozone's near collapse after the revelation of Greek public debt in late 2009. Both countries experienced a massive economic shock, as revealed by objective and subjective indicators (Chapter 3). Faced with a dire economic situation and increasing European pressure, the mainstream left in government – PS in Portugal and PSOE in Spain – announced severe austerity measures throughout 2009 and 2010 (Bremer and Vidal 2018). Consequently, the two countries saw union-organized protests against the measures early in the crisis (Accornero and Ramos Pinto 2015; Della Porta et al. 2017a; Kriesi et al. 2020; Portos 2019). Both countries experienced a turning point in 2011 when further noninstitutional actors entered the scene: Geraç\~ao à Rasca [Screwed generation] in March 2011 in Portugal and 15M (named after the first large-scale protests on May 15, 2011) in Spain. According to some estimates, almost 5 percent of the Portuguese population took to the streets on March 12, 2011 (Carvalho 2018: 98). 15M and the battle cry of the central organizing network Democracia Real, Ya! [Real democracy now] led, after the first demonstration with about 20,000 participants on Puertas del Sol, to weeks of mass protests across the country.
Keywords: 320